Penerapan Pembelajaran Kooperatif Tipe Jigsaw Untuk Meningkatkan Aktivitas Dan Hasil Belajar Siswa Kelas V SD Inpres Bhonawa - Thomasine Sofia Siganono (Ekspektasi: Jurnal Pendidikan Ekonomi, 2021)
This study aims to improve the activities and learning outcomes of students in class VA SDI Bhoanawa 1 through the application of the jigsaw cooperative learning model. This research is a classroom action research with the stages plan, action, observe and reflect. The research subjects were 15 students of SDI Bhoanaa class VA. Data obtained by observation and test techniques. Data were analyzed with simple statistics to determine the percentage of individual and classical completeness of each cycle. The results showed that after applying the Quantum learning model for two cycles there was an increase in activity and learning outcomes of Catholic Religion in class VA students at SDI Bhoanawa 1.